2016
DOI: 10.1186/s13045-016-0311-0
|View full text |Cite
|
Sign up to set email alerts
|

Modification of platinum sensitivity by KEAP1/NRF2 signals in non-small cell lung cancer

Abstract: BackgroundThe objective of this study was to evaluate the effect of platinum-based drugs on nuclear-factor erythroid2 like 2 (NRF2) signaling in non-small cell lung cancer cell lines with or without Kelch-like ECH-associated protein 1 (KEAP1) mutations and to determine the role of NRF2 and KEAP1 on platinum-based drug treatment.MethodsWe used real-time PCR to assess relative mRNA expression and used western blotting and immunofluorescence assays to assess protein expression. Small interfering RNA and shuttle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 54 publications
(65 reference statements)
3
38
0
Order By: Relevance
“…Tian et al . found that modification of Nrf2 and Keap1 expression changed cancer cell line sensitivity to platinum‐based drugs . Lee et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tian et al . found that modification of Nrf2 and Keap1 expression changed cancer cell line sensitivity to platinum‐based drugs . Lee et al .…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant signaling via the Keap1‐Nrf2 pathway frequently occurs in cancer cells, leading to the over‐activation of Nrf2 and elevation of ROS scavenging ability, facilitating the initiation and development of malignant cells that produce ROS during rapid proliferation . On the other hand, ROS are also indispensable for the therapeutic effect of platinum complexes, fluorouracil, and X‐ray, which means that Nrf2 over‐activation could also help cancer cells survive chemotherapy and irradiation and subsequently relapse …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, novel agents targeting epidermal growth factor receptor (EGFR) mutation and echinoderm microtubule-associated protein-like anaplastic lymphoma kinase (EML4-ALK) fusion benefit the patients with advanced ADC [22, 23]. Other molecular alterations, such as Notch signaling, NLK, and NRF2, also contribute to NSCLC progression [2426]. Accordingly, exploring new molecular markers is conducive to precision treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot assay was performed following the protocol as previously described [24, 25]. Briefly, the cells were harvested and lysed using ice-cold RIPA lysis buffer (50 mM Tris-HCl (pH 7.4), 150 mM sodium chloride, 1% Nonidet P-40, and 0.5% sodium deoxycholate).…”
Section: Methodsmentioning
confidence: 99%